Public participation in practice -- Assessing public participation in the preparation of regional forest programs in Northern Finland - Saarikoski, Heli; Tikkanen, Jukka; Leskinen, Leena A.
The paper analyses stakeholder involvement and public participation in preparing Regional Forest Programmes (RFP) in Finland. Such programmes establish the outlines for regional forest management, setting targets and action plans for industrial timber use, non-wood production, recreational activities, and nature conservation in each region. Our analysis suggests that the RFP process has brought together a significant cross-section of actors who meet on a regular basis. Hence, it has become an institutionalised cooperation between key stakeholder organisations. It has facilitated information exchange and learning about issues pertaining to forest management practices, timber markets, and protection of biodiversity. Engaging the general public in the RFP process has, however, been mostly ineffectual. The process has also fallen short of the expectations to reconcile different perspectives and produce jointly accepted strategies. The biggest challenges lie in finding approaches to address conflicts constructively and to draw up a RFP that will contribute to actual changes in forest management activities. Forest management planning Participatory planning Public participation Natural resources Diversity